Correlation between Six-Minutes’ Walk Test and Quality of Life in Heart Failure Patients - Syifa Rahmani; Erwinanto Erwinanto; Rudolf Andean (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: The problem of heart failure patient relates with reduced functional capacity and eventually leads to declined quality of life (QoL). Improved QoL may not relate to better functional capacity since QoL is influenced by patient’s expectation to the on-going treatment. This study was conducted to investigate the correlation between six-minutes’ walk test (6MWT) as a measure for functional capacity and QoL of heart failure patient in Dr. Hasan Sadikin General Hospital.Methods: This cross sectional study involved 32 patients who were on planned visit at the outpatient clinic of Dr. Hasan Sadikin General Hospital Bandung from September to October 2013. Subjects were chosen using consecutive sampling. The correlation of 6MWT and QoL assessed using modified Minnesota Living and Heart Failure Questionnaire (MLHFQ) was analyzed through Pearson’s correlation test.Results: There was a significant correlation between distance covered in 6MWT and QoL (r=-0.354, p<0.05).The mean of six-minute walk distance was 277.96 (±42.17) and mean of QoL score was 33.41 (±7.88). In accordance with the findings in previous studies, this study revealed correlation between the distance obtained in 6MWT and the QoL score in heart failure patient.Conclusions: There is correlation between 6MWT and quality of life in outpatients with heart failure at Dr. Hasan Sadikin General Hospital. [AMJ.2015;2(4):469–73] DOI: 10.15850/amj.v2n4.629